Haecceitism and counterpart theory. Issue 6 (30th September 2022) - De, Michael
ABSTRACT: David Lewis argues at length against haecceitism and goes as far as claiming that, on a certain counterpart‐theoretic construal, the doctrine is unintelligible or inconsistent. I argue, contra Lewis, that both qualitative and non‐qualitative counterpart theory are in fact committed to haecceitism, but that this commitment is harmless since what is really at stake for a counterpart theorist such as Lewis are more general supervenience claims that are independent of haecceitism. I further argue that Lewis's formulation of the doctrine suffers from two important defects that, once remedied, free counterpart theory of its haecceitistic commitments. Along the way I discuss an objection to the effect that the cheap substitute is inconsistent in the presence of an 'actually' operator. This paper therefore brings together important critical discussion on haecceitism and counterpart theory.